A Short Introduction to the Tiberian Masoretic Bible and its Reading Tradition. (Gorgias Handbooks, 2013)
This book is intended to provide a quick introductory overview of the Tiberian Masoretic tradition of the Hebrew Bible and its background. It was this tradition that produced the great Masoretic codices of the Middle Ages, which form the basis of modern printed editions of the Hebrew Bible. Particular prominence is given to the multi-layered nature of the Masoretic tradition. The volume contains a section describing the Tiberian reading tradition, which is essential for a correct understanding of the vocalization system.